Sea Level Rise and Shifting Maritime Limits: Stable Baselines as a Response to Unstable Coastlines - Signe Veierud Busch (Arctic Review on Law and Politics, 2018)
It is a long known fact that climate change will result in sea level rise and dramatically changed coastlines for a number of coastal States, and the physical consequences of sea level rise are most likely unavoidable for several coastal States due to their geographical location, size and topography. It is highly debatable whether the Law of the Sea Convention is equipped for dealing with the current challenges of sea level rise and maritime limits, and it may be argued that its rule of ambulatory baselines may contribute to loss of territory, relocation of maritime zones, uncertainty and instability. This article investigates the current status of the law regulating maritime limits which may be affected by sea level rise, and argues that the best solution is to adapt the law within the current legal framework of the Law of the Sea, by undertaking a liberal interpretation of the already existing provisions of the LOSC, instead of invoking the amendment procedures of the LOSC, a new supplementary agreement or creating new customary law. In particular, the article explores the option of re-interpreting the law of baselines in Article 7, offering an adapting measure that mitigates the climate change effects on sea level rise. It is argued that a liberal interpretation of the LOSC can contribute to increased stability and juridical protection of the maritime entitlements for some of the States suffering the consequences of sea level rise.